Formulação de estratégias em novos empreendimentos de alta tecnologia de origem acadêmica - Paulo Víor Guerra (2012)
Situated in the strategy management field, the formulation of strategies, characterized as a choice process which will culminate in the organization strategy, is constituted by the understanding of its meaning in the sphere of human cognition and how individuals process information for decision making. In the researches which investigate this process, a greater focus is placed on personal and external characteristics of the decision makers, and investigations which focus on understanding how strategists organize their knowledge and conduct the process of strategic decision making is less prominent, revealing, therefore, a theoretical gap. Moreover, many of these investigations aim to identify the elements considered relevant by the strategists and its determinants, and just some are concerned with the relation among these elements, called semantic nets, which results would be the formulated organizational strategy. In this sense, the research on strategy formulation in Academic New High Technology Firm (NEAT de OA, in portuguese) is specially relevant, because this specific type of organization has received a distinctive theoretical importance for theirs particularities as research objects and also empirical importance for the notable evidence on their impact on social and economic development. The present research focus on three cases of NEAT de OA as its objects of study, all of them originated in Technological and Scientific Institutions located in Minas Gerais, and pioneers in the initiative to create high technology firm aimed to develop technologies and products directed to the market, with great potential of transfers to established organizations or to generate spinoffs. To reach the proposed objectives, the present research adopts as an engaging strategy on each case the Action Research method. The data gathering is based on the modeling technique called Cognitive Mapping (CM), and uses semi-structured interviews and participant observation. Using the CM, it was possible to identify the elements which constitute the strategies and the relations among the following themes: Institutional link, Internal context, External context, Technical, Social, Human and Financial resources, and the importance attributed to these elements in the formation of the strategic meaning for the internal team and for external investors.